The complex ecological network’s resilience of the Wuhan metropolitan area - Tao Wang (Elsevier, 2021)
With rapid urbanization and frequent disasters, regional ecosystem resilience decreased continuously. Strengthening the resilience of the ecological network is conducive to improving the ecological benefits and the quality of ecological products. The research on the resilience of ecological networks is increasingly concerned, and it is necessary to construct a comprehensive research framework to evaluate the resilience of ecological networks. Taking Wuhan metropolitan area as a case, this research aimed to constructs an ecological network and evaluates network resilience from the perspective of complex networks. Firstly, we construct the evaluation Index of network resilience from the structure and function dimensions. Secondly, regions with high importance are selected as ecological sources according to the evaluation of landscape connectivity. Thirdly, the MCR model is used to establish the ecological network. Finally, we analyzed the resilience characteristics of the network under different node failure scenarios. The results show that: (1) Ecological nodes correspond to a wide variety of land types, including forest, water bodies, croplands, and urban and build-up; (2) The overall ecological connection of the ecological corridor is relatively high and the main components of the landscape are croplands, forest and water bodies; (3) The trend of structural and functional resilience does not always show convergence under different shock simulation which is related to the redundancy of networks. The research results will help to analyze the network and regional resilience and provide references for the optimization of ecological networks and the improvement of sustainable ecosystem management and restoration.